Reproductive Health Education in Adolescents - Yunita, Prasida; Mona, Silvia (HM Publisher, 2022)
Adolescence is a transition period from childhood to adulthood, covering all the development experienced in preparation for adulthood. Misinformation about sex can result in a person's knowledge and perception of the ins and outs of sex itself being wrong. Knowledge of reproductive health is indispensable to society, especially the adolescent population. The main purpose of reproductive health is to provide comprehensive reproductive health services to individuals and their partners, especially adolescents, so that each individual can aim to undergo the reproductive process. The method used in this study used counseling or direct socialization with the target, namely adolescents. The specific goal is to find out the adolescent's knowledge of reproductive health. The results showed that reproductive health counseling for adolescents is going well and is carried out by the goal, and adolescents are very enthusiastic about counseling, and very beneficial for adolescents and society. In conclusion, Counseling activities have a positive impact on adolescents and society to realize increased awareness of adolescents about how to maintain reproductive health. It is expected to be additional information about the importance of knowledge about productive health.